Characterizing Challenges in Clinical Data Modeling in RES Systems based on OpenEHR - Tuler, Elisa; Bax, Marcello; Prates, Raquel; Rocha, Leonardo (Proceedings of the Brazilian Symposium on Computing Applied to Health (SBCAS), 2014)
This work consists of analysing an important phase in the development of Electronic Health Record Systems based on OpenEHR standard, the clinical concepts modeling performed by the healthcare professionals. More specifically, our goal is to survey and analyze the existing tools, characterizing the challenges that may exist related to this phase.